2019
DOI: 10.1001/jamafacial.2018.0804
|View full text |Cite
|
Sign up to set email alerts
|

Association of Regional Facial Dysfunction With Facial Palsy–Related Quality of Life

Abstract: IMPORTANCE Study of the association of regional facial dysfunction with quality of life will lead to a better understanding of quality of life in facial palsy.OBJECTIVE To determine the association of regional facial dysfunction with facial palsy-related quality of life. DESIGN, SETTING, AND PARTICIPANTSThis retrospective cohort analysis included patients with flaccid and nonflaccid (synkinetic) facial palsy treated at a tertiary care facial nerve center; the flaccid facial palsy group included 529 patients, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 25 publications
(49 reference statements)
3
28
1
2
Order By: Relevance
“…In this study we have shown that patient-perceived synkinesis severity contributed significantly to the statistical prediction of facial palsy-related quality of life.Other variables predictive of facial palsy-related quality of life were eFace total score, gender and type of visit. The eFace total score explained 25.2% of the FaCE total score, a finding similar to other literature reports 6,10. Likewise, lower quality of life scores in female patients compared to males and the small proportional…”
supporting
confidence: 89%
See 1 more Smart Citation
“…In this study we have shown that patient-perceived synkinesis severity contributed significantly to the statistical prediction of facial palsy-related quality of life.Other variables predictive of facial palsy-related quality of life were eFace total score, gender and type of visit. The eFace total score explained 25.2% of the FaCE total score, a finding similar to other literature reports 6,10. Likewise, lower quality of life scores in female patients compared to males and the small proportional…”
supporting
confidence: 89%
“…Specifically, statistical prediction of quality of life for patients with non-flaccid facial palsy had a lower explained variance compared to that of flaccid facial palsy patients. 6 The aim of this study was to analyse whether the addition of patient-perceived severity of synkinesis to clinician-graded facial function permits better prediction of quality of life in facial palsy patients.…”
Section: Patient-perceived Severity Of Synkinesis Reduces Quality Of mentioning
confidence: 99%
“…Furthermore, function of individual facial regions seems not equally important for estimating facial palsy-related quality of life. The ability to smile seems to be of greatest importance (25). Therefore, one has to be careful with direct comparisons of the results of the different tools.…”
Section: Discussionmentioning
confidence: 99%
“…These results agree with our understanding of the typical sequelae associated with cerebrovascular accidents. First, stroke survivors typically develop unilateral facial paralysis [56], which is characterized by decreased facial symmetry during movement, and affects the patients' ability to smile [57]. Second, speech movements are commonly affected in stroke [58].…”
Section: B Detection Of Neurological Diseasesmentioning
confidence: 99%